Microfinance in Mongolia and in the Central Asian Region - Turbat, Batbayar; Janda, Karel; Leová, Simona; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2013)
The theoretical literature on Microfinance claims that Microfinance methodology can help alleviate the poverty. Mongolia is one of the countries where Microfinance is implemented and said to be successful in building a deeper and broader access to financial services. The purpose of this paper is to investigate how well Microfinance is being implemented in Mongolia and what the current practice is and, most importantly, how well the microfinance methodology works. In order to answer the last question, data collected from the proximity of the Central Asian Region including Mongolia was used. Nowadays there are number of microfinance institutions operating Mongolia such as Xacbank, Credit Mongolia. Despite the previously informal microfinance bodies such pawnshops, it appears that there was still some room on the market for Microfinance to fit in. The achievements of these Microfinance institutions are remarkable given Mongolia's extremely low population density and weak infrastructure. Research on the effectiveness of microfinance methodologies are in demand. Therefore, this paper offers research on microfinance practices such as group lending, rural lending and targeting women as well. A panel data of 90 microfinance institutions in 8 countries from the region was used. The result is rather mixed. Targeting women and lending to the rural customers seem to be working. However, group lending is found to be increasing portfolio risk and while having no effect on the financial revenue and the profitability.
Vedoucí práce: Karel Janda
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses